(untitled) (Bangladesh Journal of Medical Science, 2022)
Objective: This study was done in the ovariectomized rat model to optimize the dose ofMarantodespumilum (MP) for the treatment of open wound healing activities. Materials and Methods: Total fifty-six rats were taken for this study which was split into four groups based on four extracts such as Marantodes pumilum var. pumila (MPvp) leaf and root extracts and Marantodes pumilum var. alata (MPva) leaf and root extracts; each group contains fourteen rats. Each group was further divided into seven subgroups with equally distributed rats which consisted with one control group without treatment (Control) and six treated groups with different concentrations: 0.1% Conc, 0.5% Conc, 1.0% Conc, 2.0% Conc, 3.0% Conc and 4.0% Conc of each MP extract. After punch biopsy, rats were treated with ointment prepared by cetomacrogol emulsifying agent and MP extract on daily basis, beginning from the wound creation until healed completely. The parameters studied were the macroscopic observation andthe wound area measurement. Results: Wounds with treated 1.0% and 4.0% Conc of MPvpleaf and root extracts and 2.0%, 3.0% and 4.0% Conc of MPvaleaf and root extracts were healed completely at day 9, whereas wounds of control groups were healed at day 12 for each extract group. The wound area was significantly reduced in the treated groups with 1.0% and 4.0% Conc ofMPvpleaf and root extracts (p < 0.05) and 2.0%, 3.0% and 4.0% Conc of MPvaleaf and root extracts (p < 0.05) than their respective control group. Conclusion: The dose of 1.0% concentration for both leaf and root extracts of MPvp and 2.0% concentration for both leaf and root extracts of MPva exhibited the best effect to expedite for open wound healing compared to control group and other concentrations in the ovariectomized rat model. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 659-668